Acute hyperalgesia and delayed dry eye after corneal abrasion injury - Deborah M. Hegarty; Sam M. Hermes; Michael M. Morgan; Sue A. Aicher (PAIN Reports, 2018)
Abstract. Introduction:. Corneal nerves mediate pain from the ocular surface, lacrimation, and blinking, all of which protect corneal surface homeostasis and help preserve vision. Because pain, lacrimation and blinking are rarely assessed at the same time, it is not known whether these responses and their underlying mechanisms have similar temporal dynamics after acute corneal injury. Methods:. We examined changes in corneal nerve density, evoked and spontaneous pain, and ocular homeostasis in Sprague-Dawley male rats after a superficial epithelial injury with heptanol. We also measured changes in calcitonin gene-related peptide (CGRP), which has been implicated in both pain and epithelial repair. Results:. Hyperalgesia was seen 24 hours after abrasion injury, while basal tear production was normal. One week after abrasion injury, pain responses had returned to baseline levels and dry eye symptoms emerged. There was no correlation between epithelial nerve density and pain responses. Expression of both ATF3 (a nerve injury marker) and CGRP increased in trigeminal ganglia 24 hours after injury when hyperalgesia was seen, and returned to normal one week later when pain behavior was normal. These molecular changes were absent in the contralateral ganglion, despite reductions in corneal epithelial nerve density in the uninjured eye. By contrast, CGRP was upregulated in peripheral corneal endings 1 week after injury, when dry eye symptoms emerged. Conclusion:. Our results demonstrate dynamic trafficking of CGRP within trigeminal sensory nerves following corneal injury, with elevations in the ganglion correlated with pain behaviors and elevations in peripheral endings correlated with dry eye symptoms.